Low Mutual Coupling Dualband MIMO Microstrip Antenna with Air Gap Parasitic - Yuli Kurnia Ningsih; Rastanto Hadinegoro (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Long Term Evolution (LTE) is a standard for wireless communication of high-speed data for mobile phones and data terminals. Due to the LTE standard covers a range of many different bands in each country, therefore an antenna with more than one frequency bands become one of the most important needs in LTE antenna. In this paper, a novel triangular dual band MIMO (2x2) antenna with coplanar waveguide (CPW) fed is proposed to be used for LTE application. The proposed MIMO antenna is able to work in dual frequency that will be implemented in Indonesia at 1.8GHz and 2.35GHz. To obtain the optimum design, the characteristic of proposed antenna are numerically investigated through the physical parameters of antenna. The results show that proposed antenna has a compact size and a bandwidth of 100 MHz which is suitable for LTE application